Direct infusion analysis of nucleotide mixtures of very similar or identical elemental composition. (31st May 2013) - Quinn, Ryan; Basanta‐Sanchez, Maria; Rose, Rebecca E.; Fabris, Daniele
Abstract : The challenges posed by the analysis of mono‐nucleotide mixtures by direct infusion electrospray ionization were examined in the context of recent advances of mass spectrometry (MS) technologies. In particular, we evaluated the merits of high‐resolution mass analysis, multistep gas‐phase dissociation, and ion mobility determinations for the characterization of species with very similar or identical elemental composition. The high resolving power afforded by a linear trap quadrupole‐orbitrap allowed the complete differentiation of overlapping isotopic distributions produced by nucleotides that differed by a single mass unit. Resolving 12 C signals from nearly overlapped 13 C contributions provided the exact masses necessary to calculate matching elemental compositions for unambiguous formulae assignment. However, it was the ability to perform sequential steps of gas‐phase dissociation (i.e. MS n ‐type analysis) that proved more valuable for discriminating between truly isobaric nucleotides, such as the AMP/dGMP and UMP/ΨMP couples, which were differentiated in the mixture from their unique fragmentation patterns. The identification of diagnostic fragments enabled the deconvolution of dissociation spectra containing the products of coexisting isobars that could not be individually isolated in the mass‐selection step. Approaches based on ion mobility spectrometry‐MS provided another dimension upon which isobaric nucleotides could be differentiated according to their distinctive mobility behaviors. Subtle structural variations, such as the different positions of an oxygen atom in AMP/dGMP or the glycosidic bond in UMP/ΨMP, produced detectable differences in the respective ion mobility profiles, which enabled the differentiation of the isobaric couples in the mixture. Parallel activation of all ions emerging from the ion mobility element provided an additional dimension for differentiating these analytes on the basis of both mobility and fragmentation properties. Copyright © 2013 John Wiley & Sons, Ltd.